2020
DOI: 10.31234/osf.io/ta97c
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Revisiting status quo bias: Replication of Samuelson and Zeckhauser (1988)

Abstract: Authorship declarationGilad supervised each step in the project, conducted the pre-registrations, and ran data collection. Muhrajan Piara initiated the project, designed and analyzed the first phase of this replication project, as part of his masters dissertation. Choi Shan Lam reviewed and reanalyzed the first phase of the replication and then initiated, designed, and analyzed the data from the second phase. Qinyu Xiao reviewed the pre-registrations and verified all data analyses and drafted the manuscript. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
(76 reference statements)
0
3
0
Order By: Relevance
“…Even if the information indicated a high state, similar to subjects in the experiment, admitting to this and choosing the state associated with the lower payoff lottery was more difficult for many decision-makers [46]. Samuelson & Zeckhauser [47] and Charness & Levin [34] in their studies identified regret avoidance and a taste for consistency, respectively as a possible reason for this status quo behavior; theories for status quo bias that continue to be supported by research [48][49][50]. The deviation from optimal choices was a common occurrence throughout all stages of the pandemic.…”
Section: Hypothesis #2mentioning
confidence: 99%
“…Even if the information indicated a high state, similar to subjects in the experiment, admitting to this and choosing the state associated with the lower payoff lottery was more difficult for many decision-makers [46]. Samuelson & Zeckhauser [47] and Charness & Levin [34] in their studies identified regret avoidance and a taste for consistency, respectively as a possible reason for this status quo behavior; theories for status quo bias that continue to be supported by research [48][49][50]. The deviation from optimal choices was a common occurrence throughout all stages of the pandemic.…”
Section: Hypothesis #2mentioning
confidence: 99%
“…A sub-type of congruence bias may be the traditional confirmation bias (Nickerson, 1998) where new information is interpreted as supporting one's current beliefs. The terms have been used interchangeably in much of the empirical literature Xiao, Lan, Piara, & Feldman, 2020). In a diagnostic setting, congruence bias could lead to closing the exploratory phase prematurely; accepting a particular diagnosis before it has been fully verified, or neglecting plausible alternatives (Croskerry, 2002(Croskerry, , 2009aEva, 2001;Parmley, 2006).…”
Section: 12: Congruence Biasmentioning
confidence: 99%
“…A common barrier to amassing public support for such policies is the public's preference for existing systems and aversion to change. This phenomenon has been referred to as “status quo bias” ( 3 , 4 ). As an example, neoliberal beliefs about personal agency, behavior, responsibility, and accountability justify existing health and social systems because they presuppose that health disparities are the product of individual choices and not systemic inequalities; and therefore, changes to the system are not needed ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%